Uluslararası Piri Reis ve Türk Denizcilik Tarihi Sempozyumu, 26-29 Eylül 2013, İstanbul, bildiriler. (Ankara)
6 c. (1. c. x, 345 s. ; 2. c. x, 281 s. ; 3. c. xi, 420 s. ; 4. c. x, 294 s. ; 5. c. [x], 284 s. ; 6. c. [x], 322 s.)